Great Assets: Hungarian Children’s Classics in Teaching English to Young Learners - Palkóné Tabi, Katalin (Gyermeknevelés Tudományos Folyóirat, 2022)
The publication of more and more translations of Hungarian children’s books into English in the past two decades calls for the reconsideration of what children’s literature can be used in the English language classroom. This paper examines two Hungarian children’s books, Veronika Marék’s The Ugly Little Girl and Dóra Igaz’s Pali elkésik / Pali is Late. By exploring the teaching opportunities these books offer in the context of storytelling in TEYL (Teaching English to Young Learners), this paper argues that Hungarian children’s books in English can be used just as well as any authentic (i.e., British-American) books in language teaching. Moreover, the Hungarian culture expressed in the language and content of these books can make primary pupils more motivated and prouder of the Hungarian literary contribution to the international scene.